Islamic-Pawnbroking: a concept and perception study in Kuala Muda / Nor Adila Mohd Noor … [et al.] - Mohd Noor, Nor Adila; Aswari, Nur Alia Aqilah; Ismail, Che Zuina; Mohd Noor, Nor Azlina; Samori, Zakiah; Ahmad, Md Yazid (Academy of Contemporary Islamic Studies (ACIS), 2022)
Islamic-pawnbroking also known as the Ar-rahn plan, is a method of providing short-term financing to the public that is quick, hassle-free, and riba-free by pawning his/her jewellery to banks or any pawnshop as collateral. Ar-rahn is a secure and transparent pawnshop since it is founded on Islamic values, which vary from those of traditional pawnshops. Despite this, many people still do not trust Ar-rahn as a lender. The difficulty that Arrahn institutions confront is how to acquire clients' confidence in using the Ar-rahn scheme to ensure the safety of pawned items as compared to traditional pawnshops that have long been in Malaysia. The purpose of this study was to investigate the concept and perception of the people of Kuala Muda, Kedah towards Arrahn, as well as to identify the factors that influence the perception of Ar-rahn and to investigate the relationship between quality services and the influence of perception towards Ar-rahn. As a result, certain suggestions have been made to assist Ar-rahn institutions in gaining the confidence of their consumers via the use of the Ar-rahn plan. This study was done using the community of Kuala Muda in Kedah as respondents, and the research technique utilised was a survey approach in a qualitative study. This qualitative research technique employs a content analysis study design and a document analysis method approach in the data gathering procedure to accomplish the goals. The information and data gathered were descriptively examined. According to the findings of this research, the variables influencing consumers' impressions of the Ar-rahnu scheme in Kuala Muda are that it does not include fraudulent operations and burdens customers with low pay rates. All of these variables have a substantial impact on consumer impressions of the Ar-rahn project in Kuala Muda, Kedah.